Estimation of birthweight by measurement of fetal thigh soft‐tissue thickness improves the detection of macrosomic fetuses. (17th September 2014) - Scioscia, Marco; Stepniewska, Anna; Trivella, Giamberto; De Mitri, Paola; Bettocchi, Stefano
Abstract The accuracy of sonographic estimation of birthweight in suspected macrosomic fetuses is compromised by the imprecision of the biometrical measurements. This prospective study evaluated the performance of an equation based on linear measurement of the soft tissue above the external side of the fetal femur. The performance of this algorithm was compared with two classical algorithms. Sonographic measurements were taken within 48 h before of delivery. Sixty‐two patients with fetuses with suspected macrosomia were enrolled. The studied formulas were compared between them and showed a significant correlation with birthweight (p < 0.0001) and satisfactory statistical performances (r > 0.9). The new formula showed a reduced standard deviation that means a lower internal error in the prediction. This study supports the potential of this new approach for the estimation of birthweight in large fetuses based on sonographic linear measurements only.